2012
DOI: 10.1021/ol300366e
|View full text |Cite
|
Sign up to set email alerts
|

Carbocyclization Cascades of Allyl Ketenimines viaAza-Claisen Rearrangements ofN-Phosphoryl-N-allyl-ynamides

Abstract: A series of carbocyclization cascades of allyl ketenimines initiated through a thermal aza-Claisen rearrangement of N-phosphoryl-N-allyl ynamides is described. Interceptions of the cationic intermediate via Meerwein-Wagner rearrangements and polyene-type cyclizations en route to fused bi- and tricyclic frameworks are featured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…In suitably substituted N -phosphoryl ynamides, we demonstrated that N -promoted Meerwein-Wagner alkyl shifts could compete with the 1,2- H shift leading to fused or spiro bicyclic products. 10 In addition to exploiting the zwitter ionic intermediates via N -promoted ring expansions and contractions, we envisioned the possibility of intercepting 19 the intermediates with tethered nucleophiles to prepare a variety of bicyclic scaffolds such as 43a – 43c [Scheme 8]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In suitably substituted N -phosphoryl ynamides, we demonstrated that N -promoted Meerwein-Wagner alkyl shifts could compete with the 1,2- H shift leading to fused or spiro bicyclic products. 10 In addition to exploiting the zwitter ionic intermediates via N -promoted ring expansions and contractions, we envisioned the possibility of intercepting 19 the intermediates with tethered nucleophiles to prepare a variety of bicyclic scaffolds such as 43a – 43c [Scheme 8]. …”
Section: Resultsmentioning
confidence: 99%
“…1–3 In our own effort during the past several years, we have been heavily interested in using Pd-catalyzed and thermal aza -Claisen 4,5 rearrangements as a means of activating N -allyl ynamides towards (1) nucleophilic additions of amines 6 and alcohols, 7 (2) inter- 8 and intramolecular 9 [2 + 2] cycloaddition reactions, (3) skeletal rearrangements yielding nitriles, 6c and (4) carbocyclizations 10 and cationic polyene cascades.…”
Section: Introductionmentioning
confidence: 99%
“…DeKorver and Hsung 70 showcased a tandem aza- Claisencarbocyclization of N -phosphoryl- N -allyl-ynamides that included possibilities such as ring-expansion via Meerwein-Wagner rearrangement and polyene-type cyclizations, thereby rapidly building structural complexity leading to fused bi- and tricyclic scaffolds (Scheme 61). …”
Section: Rearrangementsmentioning
confidence: 99%
“…[10] First, it was demonstrated that ketenimine 16 was sufficiently electrophilict hat ac arbocyclization to cyclopentenyl zwitterion 17 could take place (Scheme 8). [10] First, it was demonstrated that ketenimine 16 was sufficiently electrophilict hat ac arbocyclization to cyclopentenyl zwitterion 17 could take place (Scheme 8).…”
Section: Thermal Rearrangementsmentioning
confidence: 99%